Tecnologia e mudança ocupacional: um estudo da evolução da estrutura ocupacional em Argentina e México entre 2005 e 2015 - Pontes, Danilo Moreira (2019)
The role that technical progress plays on the labor market is not only related to the amount of jobs created or destroyed but it also reflects on the distribution of different occupations over the society. Despite of the existence of many factors that impact job structure, such as education and foreign trade, technology has a central role explaining occupational change in the US and Europe, where both skill-biased technical change (SBTC) and routine-biased technological change (RBTC) hypothesis have emerged. The former reveals the skill upgrading effect determined by technological change and the latter is focused on the task content changes which lead to job polarization. By using microdata samples of national labor surveys for Argentina and Mexico in 2005 and 2015, occupations were classified according to skill level and task content group in order to assess the importance of both SBTC and RBTC hypothesis in the occupational change. As a result, there is no evidence that SBTC and RBTC had worked in the given context. Besides, changes on job structure seems to be more related to institutional and socioeconomic conditions than with technology. On the other hand, occupational change is apparently linked to the changes on industry composition, which is defined by economic development strategies historically followed by Argentina and Mexico